How do you simplify the expression #(4a^2b+8ab)/(6a^2-6a)#?

1 Answer
May 20, 2017

Answer:

See a solution process below:

Explanation:

First, rewrite the numerator and denominator by factoring out common terms:

#((4ab * a) + (4ab * 2))/((6a * a) - (6a * 1)) => (4ab(a + 2))/(6a(a - 1))#

Now, cancel common terms in the numerator and denominator:

#(4ab(a + 2))/(6a(a - 1)) => ((2 xx 2)ab(a + 2))/((2 xx 3)a(a - 1)) => #

#((color(red)(cancel(color(black)(2))) xx 2)color(blue)(cancel(color(black)(a)))b(a + 2))/((color(red)(cancel(color(black)(2))) xx 3)color(blue)(cancel(color(black)(a)))(a - 1)) => (2b(a + 2))/(3(a - 1))#